Interplay among manures, vegetable types, and tetracycline resistance genes in rhizosphere microbiome - Ali, Izhar; Naz, Beenish; Liu, Ziyang; Chen, Jingwei; Yang, Zi; Attia, Kotb; Ayub, Nasir; Ali, Ikram; Mohammed, Arif Ahmed; Faisal, Shah; Sun, Likun; Xiao, Sa; et al. (Frontiers in Microbiology, 2024)
The rapid global emergence of antibiotic-resistance genes (ARGs) presents a substantial public health concern. Livestock manure serves as a key reservoir for tetracycline resistance genes (TRGs), facilitating their transmission to soil and vegetables upon utilization as fertilizer, thereby posing a consequential risk to human health. The dynamics and transfer of TRGs amongst microorganisms in vegetables and fauna are being investigated. However, the impact of different vegetable species on TRGs acquisition from various manure sources remains unclear. This study investigated the rhizospheres of three vegetables (carrots, tomatoes, and cucumbers) grown with chicken, sheep, and pig manure to assess TRGs and bacterial community compositions via qPCR and high-throughput sequencing techniques. Our findings revealed that tomatoes exhibited the highest accumulation of TRGs, followed by cucumbers and carrots. Pig manure triggered the highest TRG levels, followed by chicken and sheep manure. Bacterial community analyses revealed distinct effects of manure sources and the selective behavior of individual vegetable species in shaping bacterial communities, explaining 12.2% of TRGs variation. Firmicutes emerged positively correlated with most TRGs and the intl1 gene among the dominant phyla. Notably, both the types of vegetables and manures significantly influenced the abundance of the intl1 gene and soil properties, exhibiting strong correlations with TRGs and elucidating 30% and 17.7% of the TRGs variance, respectively.Our study delineated high and low-risk vegetables accumulating TRGs from manure-amended soils. Moreover, elucidated the pivotal roles of bacterial communities, soil characteristics, and the intl1 gene in TRGs fate and dissemination. These insights emphasize the need for integrated strategies to reduce selection pressure and disrupt TRG transmission routes, ultimately curbing the spread of tetracycline resistance genes to vegetables.